Effective control of polarity in Bi0.9La0.1FeO3 thin films by dopant-related internal bias - Wang, Yang (2012)
The as-grown polarizations of Mn- and Ti-doped Bi0.9La0.1FeO3 thin films (BLFMn and BLFTi) are demonstrated to align in an upward direction due to the occurrence of an internal bias field Ei that points up. On the basis of the conductivity and XPS as well as leakage current measurements, Ei in BLFMn is attributed to an asymmetric distribution of charged defects, while the elevated Fermi level and broadened positively charged depletion zone are supposed to induce Ei in BLFTi. The different physical origins of Ei are intimately connected with the nature of aliovalent acceptor and donor dopants of Mn and Ti ions, which is further verified by the consistent voltage offsets in the piezoelectric hysteresis loops. This suggests an effective way to control the polarity of ferroelectric thin films through the tuning of chemical doping levels.